(1/G')-Expansion Method for Exact Solutions of (3+1)-Dimensional Jimbo-Miwa Equation - Yokuş, Asıf; Durur, Hülya (My University, 2020)
The purpose of this article is obtaining the exact solutions for (3+1)-dimensional JimboMiwa Equation (3+1DJME). The (1/G')-expansion method which is an effective method in solvingnonlinear evolution equations (NLEEs) is used. Then, 3D, contour and 2D graphics are presented bygiving special values to the constants in the solutions obtained. These graphics are a special solution ofthe (3+1DJME) and represent a stationary wave of the equation. Ready computer package program isused to obtain the solutions and graphics presented in this study.
Keywords: Fizik; Uygulamalı; Matematik